Impact of COVID-19 lockdown on undergraduate nursing and medical students of a medical college in Pokhara, Nepal (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Coronavirus disease 2019 (COVID-19) is a highly infectious disease declared a pandemic on March 11, 2020, by WHO. As a preventive measure, Nepal was put into lockdown from 24 March to 21 July, 2020 for the first wave of COVID-19 infection. Sudden lockdown prompted the widespread closure of educational institutions. This study aimed to assess the academic and social impact due to COVID-19 lockdown on undergraduate students.Method: A web based cross sectional study was conducted among 403 undergraduate students of Manipal College of Medical Sciences (MCOMS), Pokhara Nepal using the total enumeration method after the ethical approval from Institutional Review Committee (IRC), Manipal Teaching Hospital. Data was collected through online self-administered questionnaires by using Microsoft Form. Analysis of the results was done by using descriptive and inferential statistics.Result: High academic (55.6%) and social (53.8%) impact was seen in the students. Female (OR: 1.76; CI 1.1-2.82), Nepalese students (OR: 2.05; CI 1.19-3.51), data pack users (OR: 2.09; CI 1.16-3.78) were more likely to have a high academic impact. Foreign students (OR: 1.88; CI 1.11-3.11) and students having a daily update of COVID-19 (OR: 2.2; CI 1.03-4.66) were more likely to have a high social impact.Conclusion: Academic impact was seen more in female and Nepalese students while the social impact was high among foreign students. Educational activities need to continue in this critical situation. Concerned authorities need to focus on the improvement of digital infrastructure and technology along with the continuation of clinical learning with safety precautions during this pandemic time for better learning among students.